Development of a Delphi Based Ultrasonic Testing Expert System - Bagus Dwi Cahyono (Journal of Computer Science Advancements, 2023)
A person who has the expertise to operate ultrasonic testing in the field of ultrasonic called experts. Currently very difficult to obtain an ultrasonic expert in an industry. For the expert knowledge of ultrasonic testing is adopted in the computer system. This system called Expert System Type of Disability Determination Using Ultrasonic Welding The Delphi Program. This expert system is used to determine the classification of weld defects in determining the acceptance / rejection of defective welds. In the expert system can also be used to determine the type of weld defects based on defect indications obtained. In addition to the expert system there is an explanation of ultrasonic, calibration procedures and procedures for ultrasonic inspection. In the expert system is the input data that shows an ultrasonic flaw manually entered into the computer. In building an expert system software to use Delphi 7 and Inno Compiler Set Up the installer. Expert systems can be used by people who are just learning the ultrasonic as a tool to determine the acceptance / rejection of defective welds. The results showed that the Expert System Determining the type of defect indications welding able to identify all the defective welds of the inspection. Acceptance of material is observed in accordance with AWS D1.1 acceptance